Autogenic Molar Transplantation of Third Molar with Complete Root Formation Versus Incomplete Root Formation: A Prospective Clinical Study - Ankita Dixit; Rajbir K. Randhawa; Gagandeep S. Randhawa; Abhishek Nimavat; Twinkal Patel; Yesha Jani (Wolters Kluwer Medknow Publications, 2024)
Introduction: The aim of the study was to assess and compare the efficacy of autotransplantation of molars with complete and incomplete root formation, by checking the viability of the procedure to replace non-restorable molar teeth in the extraction sockets. Materials and Methods: Twenty patients with non-restorable molars were included in this study. They were divided into two groups with complete and incomplete root-formed third molars, which needed to be transplanted in place of non-restorable molars. A routine surgical procedure was performed to remove infected molars. Atraumatic removal of the third molar was performed and reimplanted in the socket of previously extracted infected molars. Results: Results were evaluated based on clinical observation and radiographic analysis of the transplanted tooth. Out of 20 transplants, one transplant, despite good initial stability, was extracted after one month because of abnormal horizontal and axial mobility; this was the single failure case (5%). Of the rest, 19/20 (95%) transplants were followed up for 6 months and showed no failure. Conclusion: This study clearly indicated that the benefits of autotransplantation over other treatment options are numerous, and the results are not affected by whether the root of the transplanted tooth is complete or incompletely formed.